2008
DOI: 10.1248/cpb.56.1270
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Leaves of Manglietia phuthoensis and Their Effects on Osteoblastic MC3T3-E1 Cells

Abstract: Osteoporosis is characterized by a reduced bone mass, which results in increased bone fragility and fracture risk. Many osteoporotic patients have already lost a substantial amount of bone; therefore, a method of increasing bone mass by stimulating new bone formation is required. Bone is composed of mineralized organic matrix and bone cells. Osteoblasts are the active mature bone cells that synthesize the organic matrix and regulate its mineralization. Accelerated osteoblast growth and protein synthesis are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Its molecular formula C 25 H 32 O 11 was deduced by the positive HR-ESIMS m/z 531.1841 [M + Na] + . The NMR of 2 were very similar to the known compound manglieside D [13]. By comparison of the NMR data in literatures, the same structure segments of a 1,3,5-trisubstituted aromatic ring, a disubstituted E -configuration double bond and a sugar unit were confirmed [18, 19].…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Its molecular formula C 25 H 32 O 11 was deduced by the positive HR-ESIMS m/z 531.1841 [M + Na] + . The NMR of 2 were very similar to the known compound manglieside D [13]. By comparison of the NMR data in literatures, the same structure segments of a 1,3,5-trisubstituted aromatic ring, a disubstituted E -configuration double bond and a sugar unit were confirmed [18, 19].…”
Section: Resultssupporting
confidence: 60%
“…The present chemical investigation led to the isolation of three new compounds ( 1–3 ) (Fig. 1), and five known compounds: manglieside D ( 4 ) [13] erythro-guaiacylglycerol- β - O -4′-coniferyl alcohol ( 5 ) [14], (+)-(7 S ,8 R )-guaiacylglycerol ( 6 ) [15], isocopoletin ( 7 ) [16], evofolin-B ( 8 ) [17] from this plant. In addition, preliminary test showed that compound 1 was a moderate antibacterial constituent against Providensia smartii with MIC value of 12.5 μg/mL, but a weak antibacterial constituent against Enterococcus faecalis and Staphylococcus aureus with MIC value of 50 μg/mL and 50 μg/mL respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a disaccharides including a -glucopyranosyl group was suggested by the characteristic chemical shifts and coupling constants of its 1 H NMR spectrum: -glucopyranosyl groupC 102.8 (C1), 74.9 (C2), 77.9 (C3), 71.6 (C4), 77.1 (C5), 68.7 (C6); H 4.80 (d, J=8.5 Hz, H1), 3.44 (dd, J=8.5, 8.5 Hz, H2), 3.40 (dd, J=8.5, 9.7 Hz, H3), 3.30 (m, H4), 3.51 (m, H5), 3.57 (dd, J=11.0, 7.3 Hz, H6a), 3 . These chemical shifts of each carbon and protons in the sugar part are very similar to those of manglieside B isolated from the leaves of Manglietia phuthoensis, 5 which possesses 6-O--D-apiofuranosyl--D-glucosyl moiety as the sugar part. The HMBC correlations confirmed the structure (in apiose; H1/C2, H1/C4, H2/C5, H4/C1, H4/C2, H4/C3, H5/C2, H5/C3, H5/C4: in Glc; H2/C3, H3/C2, H3/C4, H4/C3, H5/C3; between apiose and Glc; H1/C6).…”
Section: A R T I C L E I N F O Abstractsupporting
confidence: 60%
“…Its molecular formula, C21H29NO10, which was determined by HRESIMS at m/z 478.1709 [M+Na] + (calcd for C21H29NO10Na, 478.1689), indicated the presence of eight degrees of unsaturation in the molecule. The 1 H and 13 C NMR data of the sugar part of 2 are very similar to those of 1 and manglieside B, 5 suggesting that this compound also possessed the same disaccharide as 1 ( Table 1). The aglycon, tryptophol moiety, was determined by HMBC and COSY correlations ( Figure 2); H1/C2, H1/C2, H1/C3, H1/C3a, H2/C1, H2/C3, H2/C1, H2/C3, H2/C3a, H2/C7a, H4/C3, H4/C3a, H4/C6, H4/C7a, H5/C3a, H5/C4, H5/C6, H5/C7, H5/C7a, H6/C3a, H6/C4, H6/C7, H6/C7a, H7/C2, H7/C3a, H7/C4, H7/C5 and H1/H2, H1/H2, H4/H5, H5/H6, H6/H7.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 71%
“…activity (Piao et al, 2008), superoxide anion scavenging activities (Sasaki et al, 2013), growth and differentiation of osteoblastic MC3T3-E1 (Kiem et al, 2008), anti-HIV-1 activities (Zhang et al, 2007;Warashima et al, 2008), downregulate cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and interleukin-1b (IL-1b) gene expressions in a dose-dependent manner in LPS-elicited mouse macrophages (Ma et al, 2007), inhibited NO production (Kim et al, 2014), anti-inflammatory activity (Wu et al, 2005), antimicrobial activities (Ding et al, 2014), antiproliferative activities against human cancer cell lines (Kim et al, 2011), and neurite-outgrowth promoting activity on PC12 cells (Kuroyanagi et al, 2008). On the other hands, biological activity of 1 has been documented as antiplasmodial activity (Abrantes et al, 2008) except for our reports, to date.…”
Section: Introductionmentioning
confidence: 99%